answersLogoWhite

0


Best Answer

-2a + 5 = 1

-2a = -5 + 1

-2a = -4

a = -4/-2

a = 2

User Avatar

Wiki User

โˆ™ 2011-08-23 03:09:57
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides
๐Ÿ““
See all Study Guides
โœ๏ธ
Create a Study Guide

Add your answer:

Earn +20 pts
Q: How do you solve -2a plus 5 equals 1?
Write your answer...
Submit
Related questions

Solve the equation 2a plus 13 equals 5a 1?

If: 2a+13 = 5a+1 Then: a = 4


How do you solve fraction a plus a equals 1?

a+a=1 2a=1 a=1/2


-a plus 3a-2a equals?

1


How do you solve 8a to the third power plus one?

(2a + 1)(4a2 - 2a + 1)


What is a if 2a plus 4 equals 6?

a = 1


What is the answer to 15 - a - 2 equals 2a plus 1?

a = 4


How do you solve A plus l2l equals -1?

1


If ba equals 2a plus b then find 23 plus 32 plus 1?

If ba = 2a + b , then find 23 + 32 +1


How do you solve 6a plus 1 equals 2a plus 25?

6a+1=2a+25 Subtract 2a from both sides 4a+1=25 Subtract 1 from both sides 4a=24 Divide both sides by 4 a=6 That is your final answer.


Factor 2a squared plus 3a plus 1?

(2a+1)(a+1)


How do you solve x plus y equals 2?

Y equals 1 and X equals 1


How could you solve y equals -1x plus 2?

-1 plus 1 = 0 plus 1 =1


How do you answer 2a plus 1 equals 3?

2a + 1 = 3subtract 1 from both sides2a = 2divide both sides by 2a = 1


How do you solve 15y plus 1 equals x for y?

i have no clue what the answer is


Solve 3x plus 4y equals 11 and x plus 3y equals 2?

x = 5, y = -1


How do you solve 2a-7 equals -9?

2a - 7 = -9 2a - 7 + 7 = -9 + 7 2a = -9 +7 2a = -2 2a/2 = -2/2 a = -2/2 a= -1


Simplify 2a -3 plus 4b - 2a -b -3 plus 5?

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1


2a -3 plus 4b - 2a -b -3 plus 5?

2a-3+4b-2a-b-3+5=3b-1


What is 3a plus b-2a plus b?

1


Can you solve the cryptogram AB plus BA plus B equals AAB?

A = 1, B = 9


Simplify 7a plus 2a plus 1?

9a + 1


Simplify the expression 2a -3 plus 4b - 2a -b -3 plus 5?

3b -1


2a-4b plus 4b-6a equals a plus b?

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1


How do you solve y plus 1 divided by 3 equals 2?

y=5


How do you solve 6x plus 2 equals 1-x?

wel i cant explain how i did this but the answer is -1/7